A Real-World Retrospective Observational Study of Patients with Advanced/Recurrent Endometrial Cancer Across England - Wallis, Jamie; Luhar, Shammi; Tunaru, Filipa; Carpenter, Lewis; Wesselbaum, Anthony; Schneider, Dirk; Heffernan, Kiera; Mascialino, Barbara; Graham, Kathryn; Tookman, Laura; Roux, Rene; Ang, Joo Ern (Oncology and therapy, 2025)
Introduction Robust real-world data (RWD) on endometrial cancer (EC) are lacking. In the United Kingdom (UK), molecular classification of EC based on tumour mismatch repair (MMR) status, either MMR-deficient (dMMR) or MMR-proficient (MMRp), has been recommended at diagnosis since 2020. This study characterised patients with advanced/recurrent EC, documented treatment pathways and evaluated clinical outcomes stratified by MMR status using RWD from National Health Service (NHS) trusts in England. Methods This retrospective, observational study captured electronic health records (EHRs) from seven NHS trusts from 2000 to 2023. Clinical outcomes included overall survival (OS) and time to next treatment (TTNT). Results Data were retrieved from 731 patients with EC (79% advanced, 21% recurrent). Overall, 56.63% of patients received systemic treatment; most received platinum-based chemotherapy in first line (1L). MMR status was identified for 166 patients, with 25.30% being dMMR. Overall, 1L median TTNT was 1.22 years (95% confidence interval [CI] 1.02–1.37). Median OS from the start of 1L was 1.80 years (95% CI 1.59–2.16) in the whole cohort, 4.25 years (95% CI 1.67–not reached [NR]) in the dMMR group, 2.36 years (95% CI 2.10–2.36) in the MMRp group and 1.64 years (95% CI 1.32–1.98) in the unknown MMR group. Conclusions Although interpretation is hampered by small sample sizes, this analysis is suggestive of a difference in outcomes between MMR subgroups, underlining the importance of biomarker testing for patients with EC. Historic recording of MMR status was low; consistent testing and improvements in linking EHRs to biomarker data are needed to examine the relationship between outcomes and MMR status.